Comparison of survival between primary debulking surgery and neoadjuvant chemotherapy for stage III/IV ovarian, tubal and peritoneal cancers in phase III randomised trial. (May 2020) - Onda, Takashi; Satoh, Toyomi; Ogawa, Gakuto; Saito, Toshiaki; Kasamatsu, Takahiro; Nakanishi, Toru; Mizutani, Tomonori; Takehara, Kazuhiro; Okamoto, Aikou; Ushijima, Kimio; Kobayashi, Hiroaki; Kawana, Kei; et al.
Abstract: Background: Regarding the comparison between primary debulking surgery (PDS) and neoadjuvant chemotherapy (NACT) for stage III/IV ovarian, tubal and peritoneal cancers, EORTC55971 and CHORUS studies demonstrated noninferiority of NACT. Previously, we reported reduced invasiveness of NACT in JCOG0602. This is a final analysis including the primary endpoint of overall survival (OS). Methods: Patients were randomised to PDS (PDS followed by 8x paclitaxel and carboplatin, i.e. TC regimen) or NACT (4x TC, interval debulking surgery [IDS], 4x TC). The primary endpoint was OS. The noninferiority hazard ratio (HR) margin for NACT compared with PDS was 1·161. The planned sample size was 300. Findings: Between 2006 and 2011, 301 patients were randomised, 149 to PDS and 152 to NACT. The median OS was 49·0 and 44·3 months in the PDS and NACT. HR for NACT was 1·052 [90·8% confidence interval (CI) 0·835–1·326], and one-sided noninferiority p- value was 0·24. Median progression-free survival was 15·1 and 16·4 months in the PDS and NACT (HR: 0·96 [95%CI 0·75–1·23]). In the PDS arm, 147/149 underwent PDS and 49/147 underwent IDS. In the NACT arm 130/152 underwent IDS. Complete resection was achieved in 12% (17/147) of PDS and 31% (45/147) of PDS ± IDS in the PDS arm and in 64% (83/130) of IDS in the NACT arm. Optimal surgery (residual tumour <1 cm) was achieved in 37% (55/147), 63% (92/147), and 82% (107/130 respectively. In the NACT, PS 2/3, serum albumin ≤2·5, CA125 > 2000 an institution with low study activity was advantageous, whereas clear/mucinous histology was disadvantageous for OS. Interpretation: The noninferiority of NACT was not confirmed. NACT may not always be a substitute for PDS. However, as our study had smaller numbers, the noninferiority of the previous studies cannot be denied. Funding: Ministry of Health, Labour and Welfare, Japan and the National Cancer Center, Japan. Clinical trial information: UMIN000000523. Highlights: Survival noninferiority of NACT compared to PDS was not confirmed in this study. Noninferiority of the previous studies cannot be denied because of smaller numbers. There seems to be diversity in the efficacy of PDS/NACT among subgroups of patients.